Yield potentials, nutritional and mycochemical properties of fruit-bodies of Pleurotus ostreatus var. florida, grown on Andropogon gayanus straw; supplemented with Anthonotha macrophylla. Issue 2 (2017) - C, I.; Okwuowulu, Okwuowulu; O, E.; Ezeh, Ezeh; G, C.; Ikechukwu, Ikechukwu; C., G.
No abstract available